An Observational Study on the Diagnosis and Antibiotics Prescription in Cats with Lower Urinary Tract Disease by Veterinarians in Italy - Isabella Tirelli; Francesca Fidanzio; Simone Bertini; Serena Crosara; Luigi Intorre; Ilaria Lippi; Veronica Marchetti; Andrea Corsini (Veterinary Sciences)
Feline lower urinary tract disease (FLUTD) is a frequent diagnosis in cats, with bacterial causes constituting a minor percentage of cases. This observational study aimed to assess the diagnostic and therapeutic approaches to FLUTD among Italian veterinarians and explore variations in different workplaces. Data were collected via an anonymous survey completed by 317 veterinarians from small clinics (SC), large clinics (LC), and veterinary hospitals (VH). Results revealed that approximately half of respondents relied on clinical signs and urinalysis for diagnosis, while fewer incorporated abdominal ultrasound. Urine culture and sensitivity (UCS) testing was infrequently performed, primarily due to financial and logistical constraints, with higher compliance in VH practitioners. Antimicrobials were widely employed, with enhanced penicillins being the most prescribed class. The frequent empirical use of quinolones raises concern regarding gaps in antimicrobial stewardship. Despite some adherence to the ISCAID guidelines, discrepancies in diagnostic rigor, antimicrobial selection, and treatment duration were observed. Larger facilities demonstrated greater alignment with evidence-based practices, emphasizing the need for widespread education on appropriate antimicrobial use. This study underscores the importance of integrating guideline-based diagnostics and stewardship in managing feline urinary tract diseases.